PERANAN LEMBAGA PENELITIAN PEMERINTAH DALAM MENCERDASKAN MASYARAKAT DENGAN MOBILISASI PENGETAHUAN MELALUI MEDIA YOUTUBE - Sutarsyah Sutarsyah (Perpustakaan Nasional RI, 2019)
Goverment research institution have one of function, that is sharing their research result to the public so that they can be easily, cheaply and quickly used in order to improve the nation’s competitiveness and economic growth rate of a nation. This article aimed to find out how the govermnet institutionin the scope of LPNK Ristekdikti upload their information to the public through Youtube media. This article shows: 1. The total videos uploaded 2. The number of video uploaded every year 3. The most-viewed video 4. The most-liked video 5. The longest video. The study was carriedout using descriptive analysis method, the source of the data was from videos uploaded on Youtube from January 2016 to July 30, 2018, with keywords: LIPI, LAPAN, BPPT, BAPETEN, BATAN, and processed using Microsoft Excel. The result showed that the total of videos uploaded by 6 institution is 349 videos, with the uploaded year details are as follows: 113 videos in 2016, 135 videos in 2017, 101 videos in 2018. The most-viewed videos is : Keanekaragaman hayati” (Biodiversity) by LIPI that has reached 96, 165 views. The most-viewed like videos is “ Apa itu Big Data” (What is Big Data) by LIPI with 1,800 Likes, a video tittled “Heboh kiamat 23 september 2017, apa analisa LAPAN?” (Doomsday Judgment on September 23, 2017, what is LAPAN’s analysis?) by LAPAn becomes the most-disliked video with 25 dislike and the most commented video with 52 comments. The longest video is a live streaming show by LIPI about ecosystems that is 4 hours, 11 minutes, and 29 seconds long.